2015
DOI: 10.1093/pcp/pcv062
|View full text |Cite
|
Sign up to set email alerts
|

P450s and UGTs: Key Players in the Structural Diversity of Triterpenoid Saponins

Abstract: The recent spread of next-generation sequencing techniques has facilitated transcriptome analyses of non-model plants. As a result, many of the genes encoding enzymes related to the production of specialized metabolites have been identified. Compounds derived from 2,3-oxidosqualene (the common precursor of sterols, steroids and triterpenoids), a linear compound of 30 carbon atoms produced through the mevalonate pathway, are called triterpenes. These include essential sterols, which are structural components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
182
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 57 publications
3
182
0
Order By: Relevance
“…Identification of large numbers of DEGs in pair-wise comparisons suggests considerable transcriptional differences among tissues of T. govanianum. Additionally, important CYPs and UGTs reported to be involved in secondary metabolites biosynthesis including steroidal saponins23, showed differential expression among all the tissues supporting spatial metabolite biosynthesis in this plant. The expression analysis revealed that maximum numbers of genes were highly expressed in leaf and fruit tissues, indicating active biosynthesis of steroidal saponin in these tissues.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Identification of large numbers of DEGs in pair-wise comparisons suggests considerable transcriptional differences among tissues of T. govanianum. Additionally, important CYPs and UGTs reported to be involved in secondary metabolites biosynthesis including steroidal saponins23, showed differential expression among all the tissues supporting spatial metabolite biosynthesis in this plant. The expression analysis revealed that maximum numbers of genes were highly expressed in leaf and fruit tissues, indicating active biosynthesis of steroidal saponin in these tissues.…”
Section: Discussionmentioning
confidence: 69%
“…In plants, cycloartenol synthase and lanosterol synthase mediates the cyclization of 2,3-oxidosqualene to synthesize steroidal saponins202122. Further, several hydroxylation and glycosylation steps catalyzed by CYP450s and UGTs respectively, contributes to the structural and functional diversification of various steroidal saponins23.…”
mentioning
confidence: 99%
“…The lack of incorporation of the labeled phenylalanine into saponins is probably due to the different biosynthetic origin of these molecules. Triterpene saponins are derived from the mevalonate isoprenoid pathway, and their diversity is achieved through subsequent modifications of aglycone downstream of 2,3‐oxidosqualene cyclization (Seki et al ., ). Further support to our proposed pathways for saponin biosynthesis in Phaseolus would therefore require the use of a different labeled precursor (e.g., labeled mevalonate; Trojanowska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…UGTs are reportedly involved in triterpenoid biosynthesis in plants [22,25]. Among them, P450s have been described as the key players in diversifying triterpenoid scaffolds, and were recently identified in many triterpenoid-producing plant species [22].…”
mentioning
confidence: 99%